Manajemen Kepala Sekolah dalam Meningkatkan Minat Masyarakat pada Madrasah Ibtidaiyyah Annibros I Desa Galis Kecamatan Giligenting Kabupaten Sumenep - Kadarisman Kadarisman; Zakariyah Zakariyah (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to (1) determine how school management increases community interest in MI Annibros I, Galis Village, Giligenting District, Sumenep Regency; (2) identify the problems and solutions in the implementation of the principal's management in boosting community interest in MI Annibros I, Galis Village, Giligenting District, Sumenep Regency; and (3) assess the impact of the principal's management on enhancing community interest in MI Annibros I, Galis Village, Giligenting District, Sumenep Regency. The approach used in this research is descriptive qualitative. Data collection techniques include observation, interviews, and documentation. Data analysis involves data reduction, data presentation, and drawing conclusions. Data validity tests utilize source triangulation, technique triangulation, and time triangulation. The results show that the principal's management in increasing community interest involves creating flagship programs such as daily religious activities (Imtaq), Scouts, drum bands, English clubs, Arabic language clubs, publicizing, improving teacher quality, and enhancing infrastructure and facilities. The impact of implementing the principal's management is highly positive, as indicated by the increasing number of student admissions each year: 60 students in 2019/2020, 62 students in 2020/2021, 64 students in 2021/2022, 66 students in 2022/2023, and 67 students in 2023/2024.